Teachers Efforts in Preventing Bullying Behavior - Ansori; Anggraini, Fatik Lutviana (Tarsib: Jurnal Program Studi PGMI, 2024)
This study describes the forms and efforts of teachers in preventing bullying behavior in students at Madrasah Ibtida'iyah At-Taqwa Bondowoso. Qualitative methods produce naturalistic data in the form of reasonable explanations. Data from observations, documentation, and interviews were analyzed descriptively. The results of the study indicate that teachers' efforts in preventing bullying behavior have been maximized and are very effective and can prevent and minimize the occurrence of bullying behavior. Schools become more conducive and the learning process can run well. The success of preventing bullying in schools can be seen from the attitudes and behavior of students in everyday life who respect each other, teachers, parents and people around them, do not say bad things, act compactly and dare to take responsibility, and fear Allah by avoiding all things that are forbidden and doing what He commands.